Biodegradation of Tannins from polluted sources using natural enzymes - Tork, Sanaa Elsayed (Kuwait Journal of Science, 2020)
This study aimed to characterize an efficient tannin- degrading microorganism. Ten isolates were screened with medium supplemented with tannic acid. The highest tannase producer was the yeast; therefore, it was selected for more detail studies. Based on its morphological and biochemical characteristics, as well as phylogenetic analysis, this isolate was identified as Cryptococcus sp. NRC10 with homology level (99.9%). The optimization of factors affecting tannase production was studied. It was shown that medium II at 45°C for 24 h at pH 5 was the most favourable conditions required for maximum enzyme production. Glucose and NH4Cl proved to be the best carbon and nitrogen source, respectively. The purified enzyme was characterized. It was found that the best conditions were 0.20% of tannic acid and 0.15 ml tannase concentration at a temperature of 45°C after 10 minutes with pH 6. The addition of Mn2+ stimulates the activity of the enzyme. The purified enzyme was used for the degradation of Tannins in Red Sea water and in green tea leaves samples. It was noted a decrease in the amount of tannin after the addition of tannase enzyme. In conclusion, the enzyme has a role in the removal of Tannins in water and soil.